The Lentil: Botany, Production and Uses 2009
DOI: 10.1079/9781845934873.0076
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of economic traits.

Abstract: Although lentil is among the most prominent grain legumes globally, its economic position strengthened significantly when it became important in international trade about two decades ago. This, coupled with the International Centre for Agricultural Research in the Dry Areas (ICARDA), focused attention on the crop as its world mandate, served as a stimulus for enhanced research in the area of genetics, breeding and biotechnology. This chapter deals with the genetics of characters showing discrete, identifiable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 0 publications
0
25
1
Order By: Relevance
“…In our study, CP content was significantly and negatively correlated (r= −0.17**) with seed weight. In general, associations between CP content and seed weight have been found to be absent or weakly negative in grain legumes [25][26][27][28] and in Cajanus x Atylosia crosses [29]. These results clearly demonstrate that the relationships between seed weight and mineral and CP content vary across species and are mostly nonsignificant in grain legumes.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…In our study, CP content was significantly and negatively correlated (r= −0.17**) with seed weight. In general, associations between CP content and seed weight have been found to be absent or weakly negative in grain legumes [25][26][27][28] and in Cajanus x Atylosia crosses [29]. These results clearly demonstrate that the relationships between seed weight and mineral and CP content vary across species and are mostly nonsignificant in grain legumes.…”
Section: Resultsmentioning
confidence: 61%
“…Protein content is almost universally negatively correlated with seed size, particularly in the cereals. However, this principle does not seem to apply to the grain legumes [25]. In our study, CP content was significantly and negatively correlated (r= −0.17**) with seed weight.…”
Section: Resultsmentioning
confidence: 81%
“…In 1928, Tschermak observed a 3:1 ratio of red/orange to yellow cotyledons in reciprocal crosses between these types and reported that red/orange was dominant over yellow (Sharma 2007). In this report, it was noted that orange seed from heterozygous F 1 plants was indistinguishable from orange seed from homozygous plants.…”
Section: Qualitative Traitsmentioning
confidence: 76%
“…The consensus presently is that there are four testa color classes: black, brown, grey, and green (Sharma 2007). Black testa color is controlled by one locus with either codominance (Vandenberg and Slinkard 1990) or a dosage effect (Emami and Sharma 2000; Sharma et al 2004) that causes heterozygotes to be difficult to assigned to a discrete class.…”
Section: Qualitative Traitsmentioning
confidence: 99%
See 1 more Smart Citation